Analisa Postur Kerja terhadap Keluhan Musculoskeletal Disorder Operator Hand Stacker Menggunakan Rapid Upper Limb Assessment di PT. AFS, Makassar - Silvana Mohamad; Moh. Ainul Fais (Industrial & System Engineering Journals (ISEJOU), 2023)
Musculoskeletal Disorders is one of the injuries that workers often experience in material handling activities, namely injuries to muscles, nerves, bones, joints caused by work activities. PT. AFS as a company that focuses on catering services to serve the "airlines catering" and for the needs of companies in Makassar. A warehouse as a place to store raw materials that will continue to operate on a daily basis. In addition to the fact that the production process will continue to be connected to the warehouse, also because the raw materials that continue to come in will cause operators to continue working to organize raw materials as production supplies. An aid used to move raw materials is a hand stacker that can only be operated by one person. The use of this aid makes the operator who must be assisted by other operators to pull the hand stacker. Based on the Nordic Body Maps questionnaire, the highest pain complaints were in the lower neck, left shoulder and right shoulder. This condition is dangerous for the operator as shown by the results of RULA (score 7) with a level of category 4 (this condition is dangerous and necessary to make changes immediately).